TEMPERATURE METAPHORS IN LITHUANIAN AND ENGLISH: CONTRASTIVE ANALYSIS - Valiulienė, Edita (Verbum, 2015)
The article reports findings of a contrastive analysis of temperature metaphors and forms of their expression in two languages – Lithuanian and English. Based on corpora data, the study reveals both common tendencies and specific features of conceptual temperature metaphors and metaphorical expressions that realise them. Due to the similar physical experience and shared cultural traditions, the majority of temperature metaphors are congruent in Lithuanian and English. The features conceptualised through them are usually attributed to humans, their emotions, activities and relationships with other people. Heat as the concept of high temperature most frequently metaphorises the intensity of emotions, activities, complicated, dangerous situations. Metaphors of warmth associated with the human body conceptualise what is positive and provides comfort – pleasant feelings, sensations, friendly relationships. The targets of cold and/or coolness metaphors are the opposites of the above mentioned – the lack or absence of intensity (in the domain of emotions, activity) and negative feelings, unpleasant sensations, unfriendly relationships. The Lithuanian and English languages also share the metaphors URGENCY, RECENCY ARE HEAT and AN INITIAL STAGE IS A WARM-UP. The scope of temperature as a source domain is wider in the English language, where the concepts of heat and coolness are more productive – heat metaphors conceptualise popularity, appeal, while coolness is a metaphor for being attractive, fashionable, etc. A more frequent and varied expression of metaphors for reserve, self-control, rationality in English presumably reflects the national traits of the British character. From the linguistic point of view, metaphorical expressions differ along the following lines: grammatical status of the expression (the scope of unit, part of speech), collocability patterns and other lexico-semantic features, including derivatives, idioms, degree of conventionalisation and level of specificity. Cases of language interaction are also observed – foreign collocation patterns, new terms, semantic borrowings, English words or imitations of their phonetic form appear in Lithuanian due to cultural globalisation and the influence of the English language.